Leadership of a Clinical Academic Health Centre. (August 2019) - Allen, P. Finbarr
Abstract: The Clinical Academic Health Centre concept involves one or more health service centres forming a partnership with an academic centre, with a primary objective of leveraging of the strengths of both organisations and to hasten the process of knowledge discovery, with accelerated translation of innovations and research outcomes into clinical practice. The underpinning leadership challenge is the creation of a unified vision and mission, ensuring that strategic direction is aligned to the strategy of the major stakeholders.